Towards adequate protection of the fundamental right to secret and inviolable communications in the labor relationship: constitutional analysis in the light of new technologies - Feijóo Cambiaso, Raúl Humberto (2021)
We are currently immersed in accelerated technological progress, which brings with it both advantages for the world of communications and challenges for fundamental rights. These challenges are exemplified when talking about communications within the workplace. The phenomenon is such that both the Peruvian Supreme Court and Constitutional Court have emphasized the protection of the worker against a possible inspection by the employer of the content of his work email, unless there is a prior judicial investigation.This article analyzes the right to secrecy and inviolability of communications in labor relations from a current perspective. The axis of the research deals with the treatment of technological support provided by employers, especially the regulation of institutional emails. The author performs a comparative analysis of Peruvian, Spanish and European Court of Human Rights jurisprudence and concludes by delving into the topic of control of conversations in the worker’s social media carried out by means of an electronic support provided by the employer.